Implementación y configuración de una red lan para mejorar la conectividad en el laboratorio de desarrollo de software de la Universidad Técnica de Cotopaxi extensión La Maná periodo octubre 2014 – febrero 2015 - Moran Macías, Jonathan Alexander (2016)
The present research work originates within the Technical University of Cotopaxi in the Laboratory of Software Development because this does not count with a LAN network that enables them to develop the functions and tasks properly, this is due because currently the computing resources and the way in which data are reported have gained a great current importance within all fields of study, the speed and the way that data is transmitted to expedite the development of processes and operations; in the development of the project was used for the analysis and interpretation of the results was used an analytical methodology the same that allowed to establish the theoretical foundations that served Support for research, similarly used a field research, which helped to obtain information on the activities performed in the laboratory with the purpose of establishing the qualities that must have the LAN....